Bovine ocular squamous-cell carcinoma: lymphocyte response to phytohaemagglutinin and tumour antigen. - Jennings, P. A. (Nature Publishing Group, 1979)
The presence of ocular squamous-cell carcinomas in cattle was associated with significantly lower blastogenic response of peripheral-blood cultures to PHA than that of age-matched control cattle. The difference in blastogenic response was more marked when the external diameter of the tumour exceeded 2 cm. Cattle with aquamous-cell carcinomas had cell-mediated immunity against tumour extracts, as measured by the leucocyte adherence inhibition (LAI) microassay. The LAI reaction against tumour extracts was directly proportional to the general level of cell-mediated immunity as demonstrated by the lymphoproliferative response to PHA.